2018
DOI: 10.4038/cjs.v47i3.7530
|View full text |Cite
|
Sign up to set email alerts
|

Socio economic and health challenges of internally-displaced persons as a result of 2012 flooding in Nigeria

Abstract: Displaced people are faced with over-crowded conditions in camps with children being the most vulnerable. This is because they are faced with myriad of challenges such as poor nutrition, breakdown of health infrastructure, disease epidemics, looting and violence. Others include unprotected sex especially when separated from their families. Displaced persons are prey to a host of diseases, most of which could be prevented. In this study the socio-economic and health impacts among internally displaced persons (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Therefore, immigrants are often faced with health issues including open defecation and a lack of or inadequate water and sanitation systems. Similarly, the authors of a cross-sectional study conducted among IDPs affected by flooding in Nigeria also suggest the significant level of sickness observed among their respondents may be due to overcrowding [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, immigrants are often faced with health issues including open defecation and a lack of or inadequate water and sanitation systems. Similarly, the authors of a cross-sectional study conducted among IDPs affected by flooding in Nigeria also suggest the significant level of sickness observed among their respondents may be due to overcrowding [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study [ 10 ] reported that IDPs across three states in Nigeria who were affected by the flooding had reduced access to healthcare due to damage to the infrastructure. Specifically, only 8 (57%) of the 14 pregnant women interviewed had access to antenatal care, primarily due to a lack of money to access care and transportation to the nearest facility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission of V. cholerae and other diarrheal causing pathogens in the community is driven most often by the contamination of water sources and food products with feces due to improper disposal of fecal matter and poor personal hygiene practice (5,7). Food handlers and health workers have been identified as potential transmission portals through which other persons in the community get infected with pathogens of public health significance (2,11).…”
Section: Discussionmentioning
confidence: 99%